Epidemiological characterizations, pathogen spectrum and molecular characteristics of Coxsackievirus A16 from patients with HFMD in Yantai, Shandong, China between 2011 and 2015 - Zhenlu Sun; Guifang Zhang; Peijun Guo; Juan Liu; Qiao Gao; Xiaowen Xu; Lianfeng Gong (Human Vaccines & Immunotherapeutics, 2017)
This study aimed to investigate the epidemiological characterizations and pathogen spectrum of hand, foot, and mouth disease (HFMD) in Yantai City, Shandong Province, China, during 2011–2015, and to study the nucleotide evolution and amino acid variation of coxsackievirus A16 (CV-A16) epidemic strains that caused HFMD. The HFMD epidemic began to rise in March, and became prevalent from May to August, reached its peak in June, and then declined in September every year, children aged one to 5 years-old had the highest incidence rate whereas the incidence in children under 6 months was very low, and there were more males than females. Enterovirus nucleic acid detection using real-time reverse transcription polymerase chain reaction was performed on 2130 clinical specimens collected from patients with HFMD between 2011 and 2015, and 2012 enterovirus positive samples were detected, including 678 CV-A16, 639 EV-A71, and 695 other enteroviruses. In total, 60 CV-A16 isolates were randomly selected each year for virus isolation, of which 33 CV-A16 strains were randomly selected for further characterization because CV-A16 is the predominant serotype that caused HFMD in Yantai City, and a phylogenetic tree based on the VP1 region was constructed. All 33 CV-A16 strains belonged to the Bla and B1b genotypes, with a nucleotide similarity of 87.9–100% and deduced amino acid similarity of 98.6–100%. Compared with the reference strain Tainan/5079/98 (AF177911), amino acid mutations were identified at positions 11, 23, 25, 31, 99, 145, and 289, where differences were observed among 33 strains, indicating a unique mutation map of CV-A16 in Yantai City. Our findings demonstrate the etiologic characteristics of HFMD, provide supporting evidence for the prevention and control of HFMD, and open a promising avenue for vaccine development against HFMD, by targeting CV-A16.